The Role of Liquidity in Futures Market Innovations - Cuny, Charles J. (Review of Financial Studies, 1993)
I characterize the optimal design of a new futures market (an innovation) by an exchange in the presence of market frictions. Futures markets are characterized by both the contract and the level of trader participation; both can be determined by an exchange. A game in which exchanges simultaneously design markets is considered, and a particular equilibrium (not necessarily unique) is constructed. A game in which exchanges sequentially design markets (and incur design costs) is also considered and the (generically unique) equilibrium is constructed. The nature of equilibrium with multiple exchanges is discussed in these simultaneous and sequential settings, illustrating the role played by liquidity considerations both in market design and in the nature of competition between exchanges.